Characterisation and comparison of micropatterns written using a proton beam in Ag-activated glass and LiF crystal observed by single- and multi-photon microscopy. (June 2020) - Kurobori, Toshio; Kada, Wataru; Yanagida, Yuka; Koguchi, Yasuhiro; Yamamoto, Takayoshi; Jakšić, Milko
Abstract: We investigate the characterisation and comparison of micro-scale patterns in silver-activated phosphate glass and lithium fluoride (LiF) single crystal written by a proton beam with an energy range of 1.7–4.5 MeV. A variety of micro-scale structures based on blue and orange luminescent Ag-related colour centres in Ag-activated glass and green and red luminescent F-aggregated colour centres in LiF are visualised by combining single- and two-photon confocal microscopes equipped with a blue continuous wave (cw) laser diode and a femtosecond (fs) laser in the near-infrared (NIR) region, respectively. Two- and three-dimensional (2D and 3D) reconstructed images are analytically evaluated using lateral/axial RPL intensity mapping. In addition, the origins of different RPL intensity profiles in a plateau region along the axial direction in both materials are examined and discussed. Highlights: The micro-scale patterns in RPL Ag-activated glass written by a proton beam were visualised using two-photon microscopy. The Bragg curves of Ag-activated glass and LiF crystal were compared single-with multi-photon microscopes. The origins of different dose distribution profiles along the axial direction were investigated and discussed.